2021
DOI: 10.1002/ajb2.1784
|View full text |Cite
|
Sign up to set email alerts
|

Floral traits differentiate pollination syndromes and species but fail to predict the identity of floral visitors to Castilleja

Abstract: PremiseAnimal pollination is critical to plant reproduction and may cause convergent evolution of pollination syndromes. Pollination syndromes in Castilleja have been distinguished based on floral traits and historical observations of floral visitors. Here we addressed these questions: (1) Can pollination syndromes be distinguished using floral morphological traits or volatile organic compound emissions? (2) Is there significant variation in floral traits within a pollination syndrome at the level of populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
2
5
0
Order By: Relevance
“…In this study we characterize geographic variation in pollinator visitation and reproductive fitness across the range of four species of Castilleja. By sampling multiple populations over several years, we document a wide spectrum of visitors spanning hummingbirds, Lepidoptera (butterflies and hawkmoths), Hymenoptera (mostly small solitary bees and bumblebees) and Diptera (bee-flies and occasional hoverflies), demonstrating a diversity of visitors consistent with studies of other Castilleja species (Hersch and Roy, 2007;Hilpman and Busch, 2021). Despite exhibiting significant divergence in floral traits, we show that our four focal Castilleja species were visited broadly by all pollinator groups (with two exceptions: the lack of hummingbird visits to C. sessiliflora and of large bee visits to C. lindheimeri).…”
Section: Discussionsupporting
confidence: 72%
“…In this study we characterize geographic variation in pollinator visitation and reproductive fitness across the range of four species of Castilleja. By sampling multiple populations over several years, we document a wide spectrum of visitors spanning hummingbirds, Lepidoptera (butterflies and hawkmoths), Hymenoptera (mostly small solitary bees and bumblebees) and Diptera (bee-flies and occasional hoverflies), demonstrating a diversity of visitors consistent with studies of other Castilleja species (Hersch and Roy, 2007;Hilpman and Busch, 2021). Despite exhibiting significant divergence in floral traits, we show that our four focal Castilleja species were visited broadly by all pollinator groups (with two exceptions: the lack of hummingbird visits to C. sessiliflora and of large bee visits to C. lindheimeri).…”
Section: Discussionsupporting
confidence: 72%
“…In particular, it is common to name a proposed syndrome after its putative driver, long before such a driver has been critically examined. Pollination syndromes are one prototypical example: even studies that do not find support for pollination syndromes include statements such as "pollination syndrome was a poor predictor of [floral] visitors" (Hilpman & Busch, 2021) simply because this is the language used historically to refer to that syndrome. This results in confusing statements that appear to support the idea of a pollination syndrome when the data suggest otherwise, further obscuring the concept of a syndrome and the strength of evidence supporting (or refuting) that syndrome.…”
Section: Box 1 Definitions Of Terms Usedmentioning
confidence: 99%
“…One of the major problems in our hypothetical example is that we did not test explicitly for convergence of traits on a phylogeny. Because traits may be shared due to common ancestry rather than adaptation (Felsenstein, 1985), failing to test for convergence can give the impression of a strong relationship between traits and adaptation that are not a result of selection acting on independent lineages (see Hilpman & Busch, 2021 for a discussion of this in the context of pollination syndromes). For instance, we might travel to a third island and observe another pair of beetles.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge is to find "detectable associations between plant phenotypes and pollinators" (Waser et al 1996). Some studies have found this association (Hargreaves et al 2004;Wilson et al 2004;Pauw 2006;Geerts & Pauw 2009;Marten-Rodriguez et al 2009;Danieli-Silva et al 2012;Rosas-Guerrero et al 2014;Johnson & Wester 2017;Lagomarsino et al 2017;Bilbao et al 2021;Rose & Sytsma 2021), whereas in other cases, floral traits and pollinators were not associated, because each plant species was found to be pollinated by many kinds of animal (Waser et al 1996;Ollerton et al 2009;Hilpman & Busch 2021;Amorim et al 2022), or primarily by animals that do not match the prediction (Huang & Fenster 2007;Li & Huang 2009;Pauw et al 2020).…”
Section: Introductionmentioning
confidence: 99%